The relationship between dietary quality, serum brain-derived neurotrophic factor (BDNF) level, and the Val66met polymorphism in predicting depression. (3rd July 2019) - Froud, Amy; Murphy, Jenifer; Cribb, Lachlan; Ng, Chee H.; Sarris, Jerome
Abstract : Background: Brain-derived neurotrophic factor (BDNF), a neurotrophic factor implicated in the pathogenesis of depression, may be influenced by dietary quality. Both dietary quality and serum BDNF have been researched independently in regard to their effect on depression; however, there is limited research investigating the relationship between the two factors and how they interact in depression. Additionally, a single-nucleotide polymorphism (SNP) (Val66Met) in the BDNF gene, which has been implicated in BDNF levels and depression, may contribute to the complex relationship between depression, dietary quality, and BDNF level. Methods: One hundred and eighty-seven participants with major depressive disorder and 55 non-depressed healthy controls were recruited for this case–control analysis. The relationship between dietary quality and depression was assessed via a novel dietary quality score (the Australian Dietary Quality Score). Serum BDNF levels were measured and the Val66Met SNP was genotyped. Results: Healthy controls had a significantly higher diet quality than depressed participants ( t = 2.435, P = 0.016). A logistic regression model investigating age, sex, serum BDNF levels, dietary quality and depression, as well as any interactions, found that lower dietary quality, and surprisingly, higher BDNF levels, were associated with increased depression risk, P = 0.037 and P < 0.001, respectively. Neither seasonality (at the time of recruitment) nor the Val66Met polymorphism was associated with BDNF levels in this sample. Furthermore, there was no evidence of interaction between the Val66Met polymorphism, BDNF levels, dietary quality, and depression. Conclusion: Higher dietary quality was associated with both decreased depression incidence and severity in this cross-sectional analysis. The Val66Met polymorphism did not appear to predict BDNF levels, depression incidence, or modify the relationship between dietary quality and BDNF. Further studies utilizing a larger sample size are needed to confirm this finding.